The PENGARUH SISTEM REWARD TERHADAP KINERJA KARYAWAN DI CV. INDAH ABADI - Candra Fatihah, Dian; Farah Dilla Ade Margarheta; Ai Nunung (JEBS (Journal of Economic and Business Student), 2022)
ABSTRACT THE EFFECTS OF REWARD SYSTEM ON EMPLOYEES’ PERFOMANCE AT CV. INDAH ABADI The primary objective of this research study was to investigate the impact of rewards on employee performance at CV. Indah Abadi. This research method uses descriptive verification with data collection through field studies, questionnaires and literature studies. The sample used in this study were 35 employees of CV. Indah Abadi Based on the results of this study, the correlation coefficient value of 0.547 and it means that the effect of the reward system on employee performance at CV. Indah Abadi is categorized as moderate because it is in the range of 0.40-0.599. The results of the t hypothesis test, show that the t count score against the t table is 3.758 > 1.692 which means that there is an effect between the reward system on employee performance at CV. Indah Abadi. Based on the results of the calculation of the coefficient of determination, the value of R square of 30% means that the performance of employees at CV. Indah Abadi is affected by the reward system for 30%. CV. Indah Abadi has a problem caused by the lack of self-awareness of employees which causes the ineffectiveness of the reward system implemented by the company. Solution for the company is the reward system must be managed properly and systematically. Companies need to give rewards properly in order to make employees more motivated to complete their work. Besides to increased productivity, companies can get financial benefits if the performance of their employees is excellent. Keywords: Rewards, Employee Performance